2007
DOI: 10.1080/14034950701356435
|View full text |Cite
|
Sign up to set email alerts
|

What's new? Investigating risk factors for severe childhood malnutrition in a high HIV prevalence South African setting1

Abstract: Aim: To identify risk factors for severe childhood malnutrition in a rural South African district with a high HIV/AIDS prevalence. Design: Case-control study. Setting: Bushbuckridge District, Limpopo Province, South Africa. Participants: 100 children with severe malnutrition (marasmus, kwashiorkor, and marasmic kwashiorkor) were compared with 200 better nourished (w22 SD weight-for-age) controls, matched by age and village of residence. Bivariate and multivariate analyses were conducted on a variety of biologi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
54
2

Year Published

2010
2010
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 65 publications
(69 citation statements)
references
References 28 publications
8
54
2
Order By: Relevance
“…One recently- * US$ 1=Tk 65-the average rate during the study period; † Fisher's exact test; BCG=Bacillus CalmetteGuérin; BMI=Body mass index; CI=Confidence interval; DPT=Diphtheria, pertussis and tetanus published report from Bangladesh found a greater risk of stunting among higher birth-order children (9), and a study in South Africa found higher birthorder (>3) as a risk factor (OR=2.3, 95% CI 1.5-5.1) for all forms of severe PEM (marasmus, marasmic kwashiorkor, and kwashiorkor) (26). On the other hand, a study in Egypt did not find any relationship between birth-order and undernutrition (27).…”
Section: Discussionmentioning
confidence: 99%
“…One recently- * US$ 1=Tk 65-the average rate during the study period; † Fisher's exact test; BCG=Bacillus CalmetteGuérin; BMI=Body mass index; CI=Confidence interval; DPT=Diphtheria, pertussis and tetanus published report from Bangladesh found a greater risk of stunting among higher birth-order children (9), and a study in South Africa found higher birthorder (>3) as a risk factor (OR=2.3, 95% CI 1.5-5.1) for all forms of severe PEM (marasmus, marasmic kwashiorkor, and kwashiorkor) (26). On the other hand, a study in Egypt did not find any relationship between birth-order and undernutrition (27).…”
Section: Discussionmentioning
confidence: 99%
“…24,25 Among the benefits for an infant, breastmilk provides most of the necessary nutrients, growth factors and immunological components a healthy term infant needs. Further possible advantages of breastfeeding include reduction of incidences and severity of infections, 10,26,27,28,29,30 prevention of allergies; enhancement of cognitive development 31 and prevention of obesity, 32 , 33 , 34 , 35 , 36 , 37 &= hypertension and insulin-dependent diabetes mellitus 38 in later life as well as a possible beneficial effect on cardio-respiratory fitness in children and adolescents. 39 Analysis of data from a multicentre randomise controlled trial in Ghana, India and…”
Section: Child Healthmentioning
confidence: 99%
“…Diarrhoea is known to be a major factor contributing to undernutrition. 28 Children with severe acute malnutrition and diarrhoea on admission to a Zambian hospital were found to have over twice the odds of mortality compared with children without diarrhoea.…”
Section: Discussionmentioning
confidence: 99%